A Multi-Antenna Scheme for Early Detection and Mitigation of Intermediate GNSS Spoofing - Magiera, Jaroslaw (Sensors (Basel), 2019)
This article presents a method for detecting and mitigating intermediate GNSS spoofing. In this type of attack, at its early stage, a spoofer transmits counterfeit signals which have slight time offsets compared to true signals arriving from satellites. The anti-spoofing method proposed in this article fuses antenna array processing techniques with a multipath detection algorithm. The latter is necessary to separate highly correlated true and counterfeit GNSS signals. Spoofing detection is based on comparison of steering vectors related to received spatial components. Whereas mitigation is achieved by means of adaptive beamforming which excises interferences arriving from common direction and preserves undistorted signals from GNSS satellites. Performance of proposed method is evaluated through simulations, results of which prove the usefulness of this method for protecting GNSS receivers from intermediate spoofing interference.